Receptiveness of QRIS as a Digital Payment Among MSME in Palopo City - Jumriaty Jusman; Ika Fauziah (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
The rapid digitalization of financial transactions has led to the widespread adoption of technology-based payment systems among Micro, Small, and Medium Enterprises (MSMEs). One significant innovation in Indonesia is the Quick Response Code Indonesian Standard (QRIS), introduced by Bank Indonesia in 2019 to streamline digital payments through a unified QR code. This study explores the impact of user convenience, trust, and risk perception on QRIS user satisfaction, and further examines how these factors influence the overall use of QRIS among MSMEs in Palopo City. Using a quantitative approach, data were collected from 52 MSME actors and analyzed with SPSS V.25 to assess the relationships between variables. The results indicate that user convenience and risk perception have a significant impact on user satisfaction, while trust did not show a direct effect. Furthermore, risk perception was found to have a direct significant influence on the use of QRIS, whereas user satisfaction did not mediate the relationship between user convenience, trust, and QRIS use. The findings highlight the importance of addressing risk concerns and enhancing user satisfaction to promote broader QRIS adoption. The study contributes to the growing body of knowledge on digital payment adoption and offers practical insights for improving the user experience, particularly in regions with varying digital literacy and technological infrastructure.